A novel topology and control strategy for a soft-switched single-phase grid connected inverter - Majid Pakdel; Saeid Jalilzadeh (Journal of Electrical Systems and Information Technology, 2016)
This paper represents a novel soft switched PWM inverter topology and a control strategy using switching flow graph theory. The switching flow graph is a unique graphical model for analysis of PWM switching converters. All power switches operate at zero-voltage-switching (ZVS) turn-ON and turn-OFF conditions as a result, commutations of power switches have lower losses furthermore higher efficiency is reached. The proposed approach is analyzed theoretically and demonstrated experimentally by making a testing prototype.